Conservative Treatment for Plantar Fasciitis - Carlos Jasmin Alfredo Lobo MD (Foot & Ankle Orthopaedics, 2018)
Category: Hindfoot Introduction/Purpose: The objective of this study was to compare the results obtained in the treatment of plantar fasciitis, by: group I, muscle stretching (plantar and gastrocnemius); Group II, use of the dorsiflexion night splints; and group III, permanent elevation use of shoe heel, 2 cm or more, in relation to forefoot. Methods: One hundred and fifty patients participated in the prospective and randomized study. After randomizing the method, the patients received treatment orientation. Prescription: 150 mg diclofenac sodium, single daily dose, for 7 days. Group II, they underwent daily physiotherapy with plantar stretching and electrotherapy, associated to the use of the night splints. The evaluations were at 30 and 60 days. In the first evaluation, eight patients underwent local infiltration of betamethasone dipropionate, betamethasone disodium phosphate: five from Group I and three from Group II. All patients were evaluated on the AOFAS score of the hindfoot. Results: First evaluation: group I, 52% showed little improvement (AOFAS: initial 53.5, 30 days 56.6); Group II, 38% were dissatisfied and uncomfortable with the night splints (AOFAS: initial 55.6, 30 days 63.3). In group III, 22% of the patients reported pain arising in the morning and after periods of sitting (AOFAS: initial 57.7, 30 days 81.6). Second evaluation: Group I, AOFAS 56.9; Group II AOFAS 72.2; group III AOFAS 88.6. Conclusion: heel elevation presented a satisfactory result, superior to the other methods used; difficulty for patient’s adhesion because it eliminates usage of shoes with no heels; AOFAS / scale close to all patients treated.